To simplify the expression \( 2(3v+9)−14−6(−5v−4) \), follow these steps:
- Distribute the \( 2 \) and \( -6 \):
\[ 2(3v + 9) = 6v + 18 \]
\[ -6(-5v - 4) = 30v + 24 \]
- Replace the original expression with these simplifications:
\[ 6v + 18 - 14 + 30v + 24 \]
- Combine like terms:
-
Combine \( 6v \) and \( 30v \): \[ 6v + 30v = 36v \]
-
Combine the constant terms \( 18 - 14 + 24 \): \[ 18 - 14 = 4 \] \[ 4 + 24 = 28 \]
- Therefore, the simplified expression is:
\[ 36v + 28 \]
So the correct response is:
36v + 28.